2015
DOI: 10.3844/ajeassp.2015.302.309
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Phenolic from <i>Cleistocalyx nervosum</i> by Microwave-Assisted Extraction

Abstract: Abstract:The objective of this research was to extract phenolic compounds from Makiang (Cleistocalyx nervosum) seeds waste obtained from the elaboration of makiang beverages using the microwave assisted extraction method. The optimal conditions of microwave assisted extraction of total phenolics from makiang seeds were determined using response surface method. The variables of microwave power, extraction time and ethanol proportion on effect of total phenolic were designed the experiment by Box Behnken design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several biological activities of these berry fruits have been reported, including antiaging and neuroprotective properties, anticarcinogenicity, and immunomodulation [ 37 ]. Interestingly, a part of the seed, which is an organic waste, showed high levels of polyphenols and flavonoids [ 38 ]. However, the antineuroinflammatory studies focusing on the agricultural waste part of the seed are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological activities of these berry fruits have been reported, including antiaging and neuroprotective properties, anticarcinogenicity, and immunomodulation [ 37 ]. Interestingly, a part of the seed, which is an organic waste, showed high levels of polyphenols and flavonoids [ 38 ]. However, the antineuroinflammatory studies focusing on the agricultural waste part of the seed are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficient (R 2 ) of 0.9056 indicated that the statistical model was adequate and could represent the relationships between the Alcalase concentration (X 1 ) and hydrolysis time (X 2 ) on the DPPH radical scavenging activity (Y) of TCH. According to Narkprasom et al (2015), R 2 should be close to 1.0, but a value greater than 0.8 is acceptable. The coefficient of variation (CV) was used to describe the dispersion of the data and to represent the precision and reliability of the results.…”
Section: Response Surface Modeling and The Effect Of Factorsmentioning
confidence: 99%
“…It is mainly used for extraction because it reduces solvent usage, energy consumption, extraction times, heating rates and increases extraction efficiency and selectivity, resulting in quality target products [ 148 ]. Many studies were conducted using MAE methods on FVW and FVB, including longan seed [ 149 ], tomato peel waste [ 150 ], apple pomace [ 151 ], banana peel [ 152 ], pitaya fruit peel [ 130 , 153 ], passion fruit peel [ 130 ], lemon peel, mandarin peel, and kiwi peel [ 154 ]; thus, MAE is mostly used to extract pectin from fruit waste. This approach has been used to extract high-quality pectin with biomasses such as mango peels [ 155 ], citrus mandarin peels [ 156 ], fig skin [ 157 ], orange peel, apple pomace, mango peel, carrot pulp [ 158 ], pumpkin biomass [ 148 ], and banana peels [ 159 ].…”
Section: Innovative Technologies Used For Bioactive Compound Extractionmentioning
confidence: 99%